Proceso de Atención de Enfermería en un Paciente de 8 años de edad con Síndrome Nefrótico Corticoresistente. - Castro Benalcazar, Jazmina Madeley (2020)
Nephrotic syndrome is considered a kidney disorder, where glomeruli (blood vessels that have pores) filter large amounts of protein through urine. The most characteristic signs and symptoms of this pathology are the presence of eyelid edema and in the lower limbs, foamy urine due to the presence of proteins, asthenia, and the decrease in serum albumin and high concentrations of fat in the blood. The clinical work focused on the suffering of the corticosteroid nephrotic syndrome in an 8-year-old pediatric patient, by means of the nursing assistance which started with the respective reason for consultation, physical assessment and among the results of the assessment; The nursing care processes are formulated and developed as a result of establishing the altered functional patterns that allow the elaboration of a care plan according to the patient's requirements, follow-up; from the applied treatment as well as the type of diet to be used. Among which is taken into account the awareness and safety of the nursing staff. For the application of said treatment; In addition, educational talks were held with parents on the problems caused by the suffering of the nephrotic syndrome in the pediatric patient.